Use of an adaptive three-dimensional conductive binder in silicon-based lithium-ion batteries

CN117525425BActive Publication Date: 2026-10-30UNIV OF SCI & TECH LIAONING
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311676221.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-08
Publication Date
2026-10-30
Estimated Expiration
2043-12-08

AI Technical Summary

Technical Problem

[0012]针对现有技术中传统电极制备工艺使用导电添加剂导致的电接触损失和线型聚合物粘结剂机械性能差、粘结性差、使用有害有机溶剂和对环境污染较大,以及对于三维交联粘结剂提升硅负极锂离子电池电化学性能的机理还未明确等问题,本发明目的是在于提供一种对硅负极巨大体积变化具有良好适应能力的三维导电粘结剂,并提供了其在锂离子电池硅负极中的应用,该粘结剂表现出提升的机械性能、粘弹性和电子电导率

Benefits of technology

(1)本发明的技术方案通过使用含有丰富极性官能团的柠檬酸作为交联剂,将线性聚合物羧甲基纤维素钠和导电聚合物聚(3,4-亚乙二氧基噻吩)-聚(苯乙烯磺酸)在电极制备过程中进行原位交联,制备工艺简单,溶剂是无毒无污染的水,制得的聚合物机械性能高、导电性好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117525425B_ABST
    Figure CN117525425B_ABST
Patent Text Reader

Abstract

The application discloses application of a self-adaptive three-dimensional conductive binder in a silicon-based lithium ion battery and belongs to the technical field of lithium batteries. The three-dimensional conductive network polymer binder of the application takes citric acid (CA) as a crosslinking agent and is prepared through in-situ chemical crosslinking of sodium carboxymethyl cellulose (CMC) and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) in an electrode preparation process. The binder is applied to a silicon negative electrode of a lithium ion battery, the crosslinking density of the polymer is adjusted by controlling the concentration of the crosslinking agent, the polymer has good adaptability to the huge volume change of silicon particles in a lithiumation / delithiation process, the silicon particles are tightly packaged in a three-dimensional conductive network and do not break during deformation caused by volume expansion of the silicon particles and provide volume recovery for the silicon particles in a contraction process, the overall dynamic interface stability between components of the electrode is ensured, continuous, stable and continuous electron and ion transmission is provided for electrode reactions, the three-dimensional network structure improves the mechanical properties and adhesion of the three-dimensional conductive network, the stability of the electrode structure and the adhesion to a current collector are ensured, and the three-dimensional conductive network provides a continuous and stable electron transmission path for electrode electrochemical reactions. The synergistic effect of multiple functions effectively improves the reversible discharge specific capacity, cycle stability and rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, specifically to the preparation of a polymer that can adapt well to changes in silicon particle volume by adjusting the crosslinking density, and its application as a binder in silicon-based lithium-ion batteries. Background Technology

[0002] Since its inception, lithium-ion batteries have been widely used in various fields due to their advantages such as high energy density, good cycle performance, low self-discharge rate, and environmental friendliness. To meet the application requirements of high-power systems, such as electric vehicles, batteries with a theoretical specific capacity of 372 mAh g⁻¹ are used. -1 Commercially available graphite anode lithium-ion batteries struggle to achieve the required high energy density, excellent cycle stability, and high safety. Silicon, as the most promising anode material for lithium-ion batteries, is abundant, inexpensive, and environmentally friendly. Silicon's theoretical specific capacity (3579 mAh g⁻¹) -1 The lithium deposition potential is much higher than that of graphite anodes, and its lithium deposition potential is suitable (~0.4 V vs. Li / Li). + Silicon-based lithium-ion batteries offer high safety. The main reasons limiting their commercial application are as follows: Silicon is a semiconductor material, and its low electronic conductivity makes it difficult to use as an electrode material for power batteries; Volume changes exceeding 300% during continuous lithium delithiation / intercalation can cause silicon particles to crack and pulverize, leading to decreased cycle stability; Unstable solid-electrolyte interfaces continuously form on the silicon surface, consuming electrolyte and resulting in low initial coulombic efficiency and rapid capacity decay; Continuous volume expansion and contraction can cause the active material to separate from the current collector and from the conductive additives, resulting in loss of electrical connection and battery failure.

[0003] In recent years, to address the aforementioned challenges, numerous advanced strategies have been reported in both materials design and battery systems. These include silicon particle nanosizing, surface coating, alloying materials, core-shell structure construction, silicon-carbon composite materials, electrode pre-lithiation, and the use of electrolyte additives and functional binders. Among these, the rational design of functional binders can maintain the continuity and integrity of the contact between silicon particles, conductive additives, and current collectors, while also dissipating the stress generated by the volume effect of the silicon anode. This is a low-cost, simple, and effective method for buffering the volume expansion of the silicon anode and improving electrode dynamics.

[0004] Polyvinylidene fluoride (PVDF), a commonly used binder in lithium-ion battery electrodes, possesses advantages in chemical, electrochemical, and mechanical stability. However, its bonding mechanism with current collectors and active materials relies on weak van der Waals forces, which is insufficient to meet the requirements of high-specific-capacity anode materials such as silicon particles. Binders with abundant polar functional groups (e.g., -OH, -COOH, -(C=O)NH2) can undergo covalent and reversible non-covalent interactions with hydroxyl groups on the silicon surface, which is beneficial for maintaining the stability of the silicon anode electrode structure. Therefore, polymers containing abundant polar groups, such as gelatin, carboxymethyl cellulose, alginate, pectin, polyacrylic acid, polyvinyl alcohol, and polyacrylonitrile, have been used as binders in silicon anodes of lithium-ion batteries. However, the inherent linear structure of these binders limits their interaction with the silicon particle surface, making it difficult to suppress the irreversible slippage between the active material and the binder during continuous lithiation / delithiation processes, and failing to effectively dissipate the large stress generated by the volume expansion of silicon particles.

[0005] In comparison, three-dimensional network polymer binders can enhance mechanical properties by providing multiple inter-chain connections, thereby effectively dissipating the enormous stress generated by the volume expansion of the silicon anode and maintaining the overall stability of the electrode structure. The three-dimensional interconnected structure in the network binder can be formed through covalent interactions and supramolecular interactions (hydrogen bonds, electrostatic interactions, etc.). Chemical cross-linking between polymers through covalent bonds with high bond energy can significantly enhance the mechanical properties of the polymer, which is crucial for maintaining the integrity and stability of the electrode structure. Three-dimensional polymer network binders with supramolecular interactions can restrict irreversible slippage between silicon particles and the binder, while also possessing self-healing capabilities. Zeng et al. reported a poly(vinyltriethoxysilane) PVTES-NaPAA binder for silicon anodes. The cross-linked network is formed by the hydrolysis and subsequent condensation of the ethyl silicate groups in the PVTES-NaPAA copolymer. Test results show that the cross-linked binder outperforms uncross-linked NaPAA and other commonly used binders, achieving a capacity retention of 78.2% after 100 cycles (NaPAA 37.5%, CMC 57.9%). Furthermore, 180° peel tests demonstrated a significant improvement in adhesive strength compared to the control adhesive (RSC Advances, 2018, 8, 29230-29236). Jeena et al. covalently crosslinked the -COOH of PAA with the -OH of PVA to synthesize a covalently crosslinked multifunctional adhesive. In this copolymer, PAA provides adhesion, PVA provides flexibility, and the covalent crosslinking improves the mechanical properties of the adhesive. PAA / PVA mixtures and linear polymers, as controls, clearly showed that the three-dimensional network structure effectively buffered the stress generated by the volume expansion of the silicon anode. Compared to the linear structure, the silicon anode using the three-dimensional network structure adhesive exhibited the highest specific capacity and initial coulombic efficiency (ACS Applied Materials & Interfaces, 2014, 6, 18001-18007). In 2021, Liu et al. synthesized a stretchable elastic network polymer adhesive for silicon anodes through in-situ crosslinking of polyurethane oligomers with polyacrylic acid during electrode fabrication. In the binder CPAU, the UPy portion forms reversible quadruple hydrogen bonds. The strong tensile properties of the PEG chain can buffer the stress generated by the volume expansion of silicon particles on the binder network. The cross-linked three-dimensional network binder has high mechanical strength and significantly improves the cycle stability of the silicon anode (Acs Applied Materials & Interfaces 2021, 13 (39), 46518-46525.).

[0006] The classic process for fabricating lithium-ion battery electrodes involves mixing active materials, conductive additives, and a polymer binder dissolved in a solvent, then coating the mixture onto a metal current collector. However, silicon electrodes fabricated using this method with traditional linear binders typically exhibit poor cycle stability and rate performance. This is because the large volume changes of the silicon anode disrupt the electrode structure, and the repeated volume changes during continuous lithiation / delithiation of silicon particles cause the conductive additives to separate from the silicon particles and the current collector, failing to provide a continuous and stable electrical connection for the electrochemical reaction of the electrode, leading to rapid capacity decay. Applying conductive polymers to silicon anodes endows them with the dual functions of binder and conductive additive, providing continuous and stable electron transport for active particles during cycling, while avoiding the electrical contact loss problems caused by using inactive conductive additives. Wu et al. used phytic acid chemically pre-doped polyaniline (PANI) as a conductive binder for silicon anodes. The phosphate groups in phytic acid can form hydrogen bonds with the SiO2 layer on the silicon surface, thereby increasing the bonding force between the silicon particles and the binder. Due to its excellent conductivity and enhanced adhesion, the discharge specific capacity and cycle stability of silicon anodes using PANI binder are significantly improved at a current density of 1.0 A g. -1 After 1000 cycles, the reversible discharge specific capacity remains at 1200 mA hg. -1 (Nature Communications, 2013, 4, 1943.). Higgnis et al. used formic acid as a secondary dopant to pre-dope the PEDOT:PSS binder used for silicon anodes. They adjusted the conductivity of the Si / PEDOT:PSS electrode (80:20 wt%) by controlling the addition ratio of formic acid, achieving a maximum conductivity of 4.2 S cm⁻¹. -1 The conductivity of the Si / LiPAA / carbon black (80:10:10wt%) electrode is only 1.1 mS / cm. -1 The highly conductive Si / PEDOT:PSS electrode exhibits excellent electrochemical performance (ACS Nano, 2016, 10, 3702-3713).

[0007] The structure of polymers significantly affects their performance as binders. Three-dimensional network binders, by enhancing mechanical properties, can effectively buffer the stress caused by the large volume changes of the silicon anode, maintaining structural stability during cycling. The use of conductive polymer binders can effectively prevent the loss of electrical connection between conductive additives and active materials due to volume changes in the silicon anode. Furthermore, since conductive additives are inactive materials, the application of conductive polymer binders can also improve the battery's mass / volume capacity. However, conductive polymers can only effectively exert their high conductivity when they achieve a strong interaction with silicon particles. Without strong adhesion, even highly conductive binders cannot guarantee excellent cycle performance of the silicon anode.

[0008] Shenzhen Youbao New Materials Technology Co., Ltd. disclosed a method for preparing a three-dimensional hybrid conductive binder for lithium batteries (CN109461937A). This method introduces conductive additives such as carbon nanotubes and graphene into the binder, improving the dispersibility, electrode conductivity, and mechanical properties of the conductive additives in the polymer. The conductive network formed by the cross-linking of the conductive additives and the polymer synergistically suppresses silicon volume expansion, improving the capacity and rate performance of silicon anode lithium-ion batteries. However, this binder involves the cross-linking of inorganic conductive additives with organic polymers. During continuous lithiation and delithiation processes, the significant volume changes can lead to irreversible phase separation between the organic polymer and the inorganic conductive agent, resulting in the loss of electrical connections.

[0009] Southern University of Science and Technology (SUSTech) has disclosed a three-dimensional network aqueous composite binder (CN111180733A). This binder is formed by crosslinking an aqueous polymer emulsion and a water-soluble polymer with a crosslinking agent. It exhibits improved viscoelasticity, strong adhesion to the negative electrode material, and can buffer the damage to the electrode structure caused by volume changes of the electrode active material, maintaining the cycle stability of the lithium-ion battery. However, the preparation process of this binder is relatively complex and cumbersome. Furthermore, the binder is non-conductive, and the addition of inorganic conductive additives reduces the active material loading. Additionally, there is the problem of uneven dispersion of inorganic conductive additives in the electrode.

[0010] Changsha University of Science and Technology has disclosed the application of a carboxymethyl chitosan self-crosslinking polymer in lithium-ion battery silicon anodes (CN105702963A). This binder is formed by the self-crosslinking of carboxymethyl chitosan with the crosslinking agent 1-(3-dimethylaminopropyl)-3-ethylcarbodiamine to create a three-dimensional structure. When used as a binder in lithium-ion battery silicon anodes, it exhibits improved mechanical properties, adhesion, and self-healing capabilities. It can accommodate large volume changes in the silicon anode during charge and discharge processes, maintaining the structural stability of the electrode. The invention attributes the improved performance of the silicon anode to the enhanced mechanical properties, adhesion, and self-healing ability.

[0011] Therefore, to address the issues of poor electronic conductivity and volume effect in silicon anodes of lithium-ion batteries, a cross-linked polymer with adjustable cross-linking density and electronic conductivity was designed and prepared. This cross-linked polymer was used as a binder in silicon anodes of lithium-ion batteries. By adjusting the cross-linking density of the polymer, good adaptability to the volume changes of silicon particles during the lithiation / delithiation process was achieved, while its mechanical and electrochemical properties were optimized. Summary of the Invention

[0012] To address the problems in existing electrode fabrication processes, such as electrical contact loss due to the use of conductive additives, poor mechanical properties and adhesion of linear polymer binders, the use of harmful organic solvents and significant environmental pollution, and the unclear mechanism by which three-dimensional crosslinking binders improve the electrochemical performance of silicon anode lithium-ion batteries, this invention aims to provide a three-dimensional conductive binder with good adaptability to the large volume changes of silicon anodes and its application in silicon anodes of lithium-ion batteries. This binder exhibits improved mechanical properties, viscoelasticity, and electronic conductivity. By controlling the concentration of the crosslinking agent to adjust the crosslinking density of the polymer, good adaptability to the volume changes of silicon particles during lithiation / delithiation is achieved. It allows for volume expansion of silicon particles during complete lithiation and reversible volume recovery after complete delithiation.

[0013] This invention relates to the application of an adaptive three-dimensional conductive binder in silicon-based lithium-ion batteries. The binder with an appropriate cross-linking density tightly encapsulates silicon particles in a three-dimensional conductive network. It deforms as the silicon particles expand in volume without breaking and provides volume recovery for the silicon particles during the shrinkage process. It has good adaptability to the huge volume changes during the lithiation / delithiation process of silicon particles, maintains the integrity of the silicon anode, and effectively improves the specific capacity and cycle stability of the battery.

[0014] To achieve the above technical objectives, this invention provides an application of an adaptive three-dimensional conductive binder in silicon-based lithium-ion batteries. This application involves crosslinking poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) with electronic conductivity to sodium carboxymethyl cellulose using citric acid as a crosslinking agent in situ thermal initiation, and then using it as a binder on the silicon anode of a lithium-ion battery.

[0015] The technical solution of this invention is: This invention discloses an adaptive three-dimensional conductive binder using citric acid as a crosslinking agent. It is prepared by in-situ crosslinking of sodium carboxymethyl cellulose and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) during electrode fabrication. The mass percentages of sodium carboxymethyl cellulose, citric acid, and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) added are 1~20 wt%: 1~20 wt%: 1~20 wt%. The crosslinking density of the three-dimensional conductive network polymer binder is adjusted by controlling the concentration of citric acid. The abundant polar groups of citric acid enhance the adhesiveness of the binder through dynamic hydrogen bonding and electrostatic interactions. Through covalent and reversible non-covalent crosslinking, a three-dimensional conductive network structure is formed in the binder. The silicon electrode using the three-dimensional conductive network polymer binder is prepared through the following steps: S1) Dissolve sodium carboxymethyl cellulose in deionized water to prepare a 9 wt% sodium carboxymethyl cellulose solution; S2) Add 5 wt% citric acid and 6 wt% poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) sequentially to the sodium carboxymethyl cellulose solution and stir for 5 hours to completely dissolve and mix evenly; S3) Place the above binder solution and 80wt% silicon powder (30nm) in a mortar and grind for 20~30min; S4) Place the above electrode paste on copper foil and apply it to the electrode using a doctor blade to fix the thickness; S5) Place the above electrodes in a vacuum drying oven and dry them at 80°C for 12 h, then crosslink them in situ at 150°C for 6 h. S6) Cut the above material into electrode discs with a diameter of 12 mm to obtain silicon electrodes using a three-dimensional conductive network polymer binder.

[0016] Furthermore, the in-situ crosslinking is achieved by using citric acid as a crosslinking agent and covalently crosslinking it with sodium carboxymethyl cellulose and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) through an esterification reaction.

[0017] Furthermore, the polymer crosslinking density is adjusted by controlling the mass percentage of citric acid, which is 1~20 wt%.

[0018] Furthermore, the sodium carboxymethyl cellulose has a viscosity ≥1900 mPa·s, the poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) concentration is 1.5% in aqueous solution, and the citric acid has a molecular weight of 192.

[0019] Furthermore, the silicon material is silicon powder with a particle size of 30~500nm, the silicon powder accounts for 60~95 ​​wt% of the total mass of the electrode material, the three-dimensional conductive network polymer binder accounts for 5~40 wt% of the total mass of the electrode material, and the total mass content of the two components is 100 wt%.

[0020] Furthermore, the coating thickness in step S4) is 10~30μm.

[0021] Furthermore, the crosslinking temperature in step S5) is 120~160℃.

[0022] The mechanism of this invention involves in-situ crosslinking of a polymer binder during electrode fabrication. Citric acid, rich in carboxyl and hydroxyl groups, is used as the crosslinking agent. It chemically crosslinks with a water-soluble linear polymer, sodium carboxymethyl cellulose, and a conductive polymer, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid), through thermal initiation. This chemical crosslinking primarily occurs via esterification, and the crosslinking density of the three-dimensional conductive polymer network is precisely adjusted by controlling the citric acid concentration. The three-dimensional network polymer binder with a suitable crosslinking density exhibits good adaptability to the volume changes of silicon particles during lithiation / delithiation. It allows for volume expansion of silicon particles during complete lithiation and reversible volume recovery after complete delithiation, thereby improving the discharge specific capacity, cycle stability, and rate performance of silicon anode lithium-ion batteries.

[0023] Esterification, the condensation of carboxyl and hydroxyl groups in polymer molecules to form bonds, is a common reaction for preparing cross-linked network adhesives, resulting in high-energy and high-strength covalent bonds. The abundant polar groups in the adhesive molecule effectively enhance its adhesion to silicon particles and current collectors. Based on these reasons, the preferred embodiment of this invention is to chemically cross-link sodium carboxymethyl cellulose and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) through an esterification reaction. The hydroxyl and carboxyl groups in the reactant citric acid can covalently cross-link sodium carboxymethyl cellulose and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), respectively. The abundant polar groups (carboxyl and hydroxyl groups) in the reactants can also form hydrogen bonds and electrostatic interactions with the hydroxyl groups on the silicon surface, enhancing adhesion.

[0024] The viscoelasticity enhanced by the adaptive three-dimensional conductive network polymer binder has good adaptability to the volume expansion and contraction of silicon particles during the lithiation / delithiation process. The binder with appropriate crosslinking density tightly encapsulates the silicon particles in the three-dimensional conductive network, deforms with the volume expansion of the silicon particles without breaking, and provides reversible volume recovery for the silicon particles during the contraction process.

[0025] Compared with the prior art, the beneficial effects of the present invention are: (1) The technical solution of the present invention uses citric acid containing abundant polar functional groups as a crosslinking agent to perform in-situ crosslinking of linear polymer sodium carboxymethyl cellulose and conductive polymer poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) during electrode preparation. The preparation process is simple, the solvent is non-toxic and non-polluting water, and the obtained polymer has high mechanical properties and good conductivity.

[0026] (2) The technical solution of the present invention accurately adjusts the crosslinking density of the three-dimensional conductive polymer network by adjusting the concentration of the crosslinking agent citric acid. The appropriate crosslinking density has good adaptability to the volume change of silicon particles during the lithiation / delithiation process, thereby constructing a continuous and stable three-dimensional conductive path on the surface of silicon nanoparticles. This allows the silicon particles to be tightly encapsulated in the three-dimensional conductive polymer network during the continuous charge and discharge volume change process. The silicon particles are allowed to expand in volume during complete lithiation and achieve reversible volume recovery after complete delithiation, ensuring continuous and stable electron and ion transport during the electrode electrochemical reaction process.

[0027] (3) The abundant carboxyl and hydroxyl groups in the polymer binder of the present invention can form covalent bonds and supramolecular interactions with silicon particles and current collectors, thereby enhancing the bonding force between materials and the adhesion to the current collector.

[0028] (4) The conductive polymer poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) grafted in the polymer binder of the present invention gives the binder electronic conductivity. Without the addition of non-active conductive additives, it effectively avoids the phenomenon of loss of electrical connection between the components of the electrode due to the volume expansion of silicon particles, improves the mass / volume specific capacity of the battery, and the constructed three-dimensional conductive network also provides a stable and continuous electron transport path for electrochemical reactions.

[0029] (5) The polymer binder of the present invention has a three-dimensional interconnected network structure. The improved mechanical properties and peeling force on the current collector can effectively buffer the stress generated by the huge volume change of the silicon anode of lithium-ion battery during the cycle charge and discharge process, and solve the problem of poor structural integrity and stability of silicon anode during the cycle.

[0030] (6) The polymer binder of the present invention has strong adhesion, does not dissolve, decompose or react in the electrolyte, and has strong chemical and electrochemical stability, which can effectively improve the electrochemical performance of silicon anode lithium-ion batteries.

[0031] (7) The three-dimensional conductive network polymer binder of the present invention has good adaptability to the volume expansion and contraction of silicon particles during the lithiumation / delithiation process. The binder with a suitable crosslinking density tightly encapsulates the silicon particles in the three-dimensional conductive network. It deforms with the volume expansion of the silicon particles without breaking and provides volume recovery for the silicon particles during the contraction process, ensuring the overall dynamic interface stability between the various components of the electrode, providing continuous, stable and continuous electron / ion transport for the electrode reaction, and improving the battery specific capacity and cycle stability.

[0032] (8) The raw materials for preparing the adhesive of the present invention are widely available, the reaction conditions are mild, the reaction rate is fast, the solvent used is water, the preparation process is safe, green and environmentally friendly, the steps are simple, the process is simple and easy to control, the feasibility is high, and it is suitable for large-scale commercial production. Attached Figure Description

[0033] Figure 1 This is the infrared spectrum of a three-dimensional conductive network polymer binder (CCP); Figure 2 This is a graph showing the relationship between peel force and displacement in a 180° peel test using electrodes with different adhesives; Figure 3 These are the nanoindentation curves of CCP, CMC, and PVDF adhesives; Figure 4 This is the dependence of the elastic modulus (G′) and viscous modulus (G″) of CCP adhesives with different citric acid concentrations on angular frequency; Figure 5 CCP binder silicon anodes prepared using different citric acid concentrations at 2000 mA g -1 Comparison of cycling performance at current density; Figure 6 This is a diagram illustrating the mechanism of action of silicon anodes with different crosslinking densities prepared using different citric acid concentrations and CCP binders. Figure 7 Silicon anodes using different binders at 500 mA g -1 Comparison of cycling performance at current density; Figure 8 Silicon anodes using different binders have a g-value of 200~8000 mA. -1 Comparison of cycling performance at current density; Figure 9 These are SEM images of the surface morphology of silicon anodes using different binders before and after 100 cycles. Figure 10 These are high-magnification SEM images of the surface morphology of silicon anodes using different binders before and after 100 cycles. Detailed Implementation

[0034] The present invention will be further described in detail below with reference to embodiments, but this does not constitute any limitation on the scope of protection of the claims of the present invention, and is only used to help understand the content of the present invention. Example 1

[0035] Preparation of silicon electrodes using citric acid as a crosslinking agent with a concentration of 5 wt% three-dimensional conductive network polymer binder (CCP) and their application in lithium-ion batteries: 1) Dissolve 9 mg of sodium carboxymethyl cellulose (CMC) in deionized water to prepare a 9 wt% CMC solution; 2) Add 5 mg of citric acid (CA) to the above solution and stir to dissolve; 3) Add 6 mg of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS) to the above solution, stir for 3 hours, and mix thoroughly; 4) Weigh 80mg of silicon powder (30nm) and place it in a mortar. Grind it thoroughly with the above binder solution for 20-30 minutes. 5) Place the electrode paste obtained in step 4) onto the copper foil and apply it evenly with a scraper to fix the thickness; 6) The electrode was placed in a vacuum drying oven and dried at 80℃ for 12 h, then cross-linked in situ at 150℃ for 6 h before punching to obtain a circular electrode sheet with a diameter of 12 mm. The loading amount of silicon nanoparticles on the copper foil was controlled to be 0.8~0.9 mg / cm² by controlling the height of the doctor blade. -2 ; 7) Place the electrode obtained in step 6) in a glove box filled with argon gas, use a lithium metal sheet as the reference electrode, 1M LiPF6 (DMC:FEC=4:1 Vol%) as the electrolyte, and assemble a half cell with a diaphragm manufactured by Gelgard.

[0036] The infrared spectrum of the prepared three-dimensional conductive network polymer CCP is as follows: Figure 1 As shown, CMC and PEDOT:PSS covalently crosslinked with the carboxyl and hydroxyl groups of CA through esterification reactions.

[0037] The electrode sheet prepared in this embodiment was cut into 10mm*40mm samples. The side of the electrode coated with slurry was adhered to a steel sheet using 3M tape. The lower end of the sample was fixed on a tensile testing machine at room temperature and subjected to a tensile test at 100mm min. -1 A constant rate was used to perform a 180° peeling experiment on the electrode sheet. For example... Figure 2 As shown, compared to electrodes using other adhesives, the CCP adhesive electrode has the highest average peel force, at 537 mN.

[0038] The mechanical properties of the polymer binder were tested using nanoindentation experiments, and the resilience was calculated. For example... Figure 3 As shown, at the same indentation depth, the CCP binder exhibits the greatest indentation force, indicating that the CCP binder has the best mechanical properties. The rebound rate of the CCP binder, calculated using the nanoindentation curve, is the highest at 49.03%. This means that the excellent viscoelasticity of the CCP binder allows it to stretch with the volume expansion of silicon particles and recover to its initial state with their volume contraction, effectively maintaining the integrity and stability of the electrode structure.

[0039] The crosslinking density of the CCP (CA=5.0) binder prepared with a CA addition ratio of 5.0 wt% in this embodiment was determined by rheological testing. Figure 4 The changes in elastic modulus (G′) and viscous modulus (G′′) of polymer solutions with different amounts of crosslinking agent are shown. The curves show the coexistence of G′ and G′′ at all frequencies, indicating that the CCP binder possesses both elasticity and viscosity. By adjusting the crosslinking agent concentration to control the crosslinking density and network strength of the polymer solution, the crosslinking density of the CCP (CA=5.0) binder is moderate.

[0040] The charge-discharge performance of half-cells assembled using CCP (CA=5.0) adhesive was tested using a LAND-CT3002A tester, with a current density of 2000 mA g. -1 Set the voltage range to 0.01~1.5V. For example... Figure 5 As shown, the Si / CCP (CA=5.0) electrode at 2000 mA g -1 It exhibits superior cycling stability at the specified current density, with a capacity retention of 54.91% after 300 cycles. This is due to the optimal cross-linking density of the three-dimensional conductive network formed by chemical cross-linking at a CA concentration of 5.0 wt%. This network exhibits good adaptability to the volume changes of silicon particles during lithiation / delithiation. The conductive, highly viscoelastic, and strongly adhesive polymer network tightly wraps around the surface of each silicon particle, maintaining the dynamic stability of the overall interface between silicon and the binder during repeated volume expansion and contraction. This provides a continuous and stable electrical connection for the electrode reaction, while the improved mechanical properties help maintain the integrity and stability of the electrode, thereby effectively improving electrochemical performance. Figure 6 As shown.

[0041] The charge-discharge performance of the half-cell assembled using CCP binder was tested using a LAND-CT3002A tester, with a current density of 500 mA g. -1 Set the voltage range to 0.01~1.5V. For example... Figure 7 As shown, the assembled lithium-ion half-cell achieves a first-discharge specific capacity of 3841 mAh g⁻¹. -1The initial coulombic efficiency was 88.57%, and the capacity retention after 100 consecutive charge-discharge cycles was 84.7%, showing significant improvements in initial discharge specific capacity, initial coulombic efficiency, and cycle stability. The CCP binder silicon anode performed well even at 8000 mA g... -1 It can still maintain a high reversible discharge specific capacity (1166.6 mAh g) at current density. -1 When the current density recovers to 500 mA g -1 When the silicon anode using CCP binder is applied, it can return to its initial state. This indicates that CCP can effectively maintain the stability of the electrode structure even at high current densities. Furthermore, the electronic conductivity of the binder is beneficial for improving electrode reaction kinetics, thereby enhancing the rate performance of the silicon anode. Figure 8 As shown.

[0042] To further understand the role of using a three-dimensional conductive network polymer binder in maintaining the integrity of the silicon anode, the surface morphology of the electrode before cycling and after 100 cycles was compared. Figure 9 As shown, the silicon anode using CCP binder has a uniform and smooth electrode surface before cycling. After 100 cycles, the electrode develops relatively fine and fewer cracks. This is because the improved mechanical properties of the three-dimensional network structure formed by in-situ crosslinking effectively dissipate the stress generated by the volume expansion of silicon particles, which is beneficial to maintaining the structural stability of the silicon anode during cycling. The surface morphology of the silicon anode using CCP binder after 100 cycles was observed using SEM. Figure 10 As shown, a thinner and more stable SEI is formed on the surface of silicon particles using CCP binder. This is because the three-dimensional network structure formed by cross-linking is well-adapted to the volume changes of silicon particles during lithiation / delithiation, allowing for volume expansion of silicon particles during complete lithiation and reversible volume recovery after complete delithiation. The improved mechanical properties effectively buffer the stress generated by the volume expansion of the silicon anode, reducing the damage to the SEI film caused by the volume expansion of silicon particles and avoiding the formation of continuous SEI.

[0043] Comparative Example 1 Preparation of silicon electrodes using CMC binder and their application in lithium-ion batteries: 1) Dissolve 10 mg of sodium carboxymethyl cellulose (CMC) in deionized water to prepare a 10 wt% CMC solution; 2) Weigh 80 mg of silicon powder (30 nm) and 10 mg of conductive additive (Super P), place them in a mortar, and grind them thoroughly with the above binder solution for 20-30 minutes; 3) Apply the slurry obtained in step 2) onto the copper foil to fix the thickness and uniformly coat the electrode; 4) After vacuum drying at 80℃ for 12 h in a vacuum drying oven, the electrode is punched to obtain a circular electrode sheet with a diameter of 12 mm. The loading of nano-silicon particles on the copper foil is controlled to be 0.8~0.9 mg / cm² by controlling the height of the coating doctor blade. -2 ; 5) Place the electrode obtained in step 4) in a glove box filled with argon gas, use a lithium sheet as the reference electrode, 1M LiPF6 (DMC:FEC=4:1 Vol%) as the electrolyte, and assemble a half cell with a diaphragm manufactured by Gelgard.

[0044] The electrode sheet prepared in this comparative example was cut into 10mm*40mm samples. The side of the electrode coated with the slurry was adhered to a steel sheet using 3M tape. The lower end of the sample was fixed on a tensile testing machine at room temperature and subjected to a tensile test at 100mm min. -1 A constant rate was used to perform a 180° peeling experiment on the electrode sheet. For example... Figure 2 As shown, the average peel force of CMC adhesive is 139 mN, which is significantly lower than that of CCP adhesive.

[0045] The mechanical properties of the polymer binder were tested using nanoindentation experiments, and the resilience was calculated. For example... Figure 3 As shown, at the same indentation depth, the indentation force of CMC adhesive is lower than that of CCP, indicating that the mechanical properties of CMC adhesive are relatively poor. The rebound rate of CMC adhesive, calculated using nanoindentation curves, is 48.28%, indicating that CMC adhesive has poorer viscoelasticity compared to CCP adhesive.

[0046] The charge-discharge performance of the half-cell assembled using CMC binder was tested using a LAND-CT3002A tester, with a current density of 500 mA g. -1 Set the voltage range to 0.01~1.5V. For example... Figure 7 As shown, the first discharge specific capacity of the assembled lithium-ion half-cell is 3255 mAh g. -1 The initial coulombic efficiency was 89.06%, and the capacity retention after 100 charge-discharge cycles was 35.8%. Compared with silicon anodes using three-dimensional conductive network polymer binders (CCP), its initial discharge specific capacity and cycle stability were poorer. This indicates that although the abundant polar groups in the CMC molecular structure can form strong non-covalent interactions with silicon particles, its inherent linear structure makes it difficult to buffer the stress generated by the volume expansion of the silicon anode. After continuous cycling, the destruction of the electrode structure leads to the loss of electrical contact between the silicon particles and the current collector and conductive additives, resulting in low discharge specific capacity and poor cycle stability. Silicon anodes using CMC binders showed better performance at 8000 mA g⁻¹. -1 The reversible discharge specific capacity at the current density is 132.6 mAh g. -1When the current density recovers to 500 mA g -1 When the reversible capacity of the silicon anode using CMC binder cannot be restored to its initial state, it indicates that the structure of the electrode using CMC binder is damaged at higher current densities, resulting in poor rate performance. Figure 8 As shown.

[0047] To further understand the changes in electrode surface morphology during cycling of silicon anodes using CMC binder, the surface morphology of the electrodes before and after 100 cycles was compared. Figure 9 As shown, the silicon anode using CMC binder developed numerous cracks on its surface after 100 cycles. The surface morphology of the silicon anode using CMC binder after cycling was observed at higher magnification using SEM. Figure 10 As shown, a relatively thick SEI film formed on the surface of the silicon particles using CMC binder after 100 cycles.

[0048] Comparative Example 2 Preparation of silicon electrodes using PVDF binder and their application in lithium-ion batteries: 1) Dissolve 10 mg of polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) to prepare a 10 wt% PVDF solution; 2) Weigh 80 mg of silicon powder (30 nm) and 10 mg of conductive additive (Super P), place them in a mortar, and grind them thoroughly with the above binder solution for 20-30 minutes; 3) Apply the slurry obtained in step 2) onto the copper foil to fix the thickness and uniformly coat the electrode; 4) After vacuum drying at 80℃ for 12 h in a vacuum drying oven, the electrodes were punched to obtain circular electrode sheets with a diameter of 12 mm. The loading of nano-silicon particles on the copper foil was controlled to be 0.8–0.9 mg / cm² by controlling the height of the coating doctor blade. -2 ; 5) Place the electrode obtained in step 4) in a glove box filled with argon gas, use the electrode as a reference electrode, 1M LiPF6 (DMC:FEC=4:1 Vol%) as the electrolyte, and assemble a half cell with a diaphragm manufactured by Gelgard.

[0049] The electrode sheet prepared in this comparative example was cut into 10mm*40mm samples. The side of the electrode coated with the slurry was adhered to a steel sheet using 3M tape. The lower end of the sample was fixed on a tensile testing machine at room temperature and subjected to a tensile test at 100mm min. -1 A constant rate was used to perform a 180° peeling experiment on the electrode sheet. For example... Figure 2 As shown, the PVDF adhesive has the lowest average peel force, at 76 mN.

[0050] The mechanical properties of the polymer binder were tested using nanoindentation experiments, and the resilience was calculated. For example... Figure 3 As shown, compared with CCP and CMC binders, PVDF exhibits the lowest indentation force at the same indentation depth, indicating that PVDF binder has the worst mechanical properties. The rebound rate of PVDF binder, calculated using nanoindentation curves, is 42.63%. Its poor mechanical properties and viscoelasticity make it unable to adapt to the significant volume changes of silicon particles during continuous lithiation / delithiation, making it difficult to maintain the integrity of the electrode structure and leading to rapid capacity decay in the battery.

[0051] The charge-discharge performance of half-cells assembled using PVDF binder was tested using a LAND-CT3002A tester, with a current density of 500 mA g / g. -1 Set the voltage range to 0.01~1.5V. For example... Figure 7 As shown, the first discharge specific capacity of the assembled lithium-ion half-cell is 2669 mAh g. -1 The initial coulombic efficiency was 63.48%, and the capacity retention after 100 consecutive charge-discharge cycles was 19.6%. The silicon anode using PVDF binder performed well at 8000 mA g. -1 The reversible discharge specific capacity at the current density is 18.3 mAh g. -1 When the current density recovers to 500 mA g -1 When using PVDF binder, the reversible capacity of the silicon anode cannot be restored to its initial state, and its rate performance is as follows: Figure 8 As shown.

[0052] To further understand the changes in electrode surface morphology of silicon anodes using PVDF binder during cycling, the surface morphology of the electrodes before cycling and after 100 cycles was compared. Figure 9 As shown, the silicon anode using PVDF binder exhibited surface cracking after 100 cycles, indicating severe damage to the electrode structure. The surface morphology of the silicon anode using PVDF binder after cycling was observed at higher magnification using SEM. Figure 10 As shown, a thick SEI film is formed around the silicon particles using PVDF binder. The thicker SEI connects the silicon particles into sheets because the weak van der Waals forces of PVDF make it difficult to maintain the stability of the electrode structure during cycling. The volume expansion of the silicon particles leads to the formation of continuous SEI.

[0053] Comparative Example 3 Preparation of silicon electrodes using citric acid as a crosslinking agent and 0 wt% polymer binder CP (CA=0) and their application in lithium-ion batteries: 1) Dissolve 9 mg of CMC in deionized water to prepare a 9 wt% CMC solution; 2) Add 6 mg of PEDOT:PSS to the above solution and stir for 3 hours until well mixed; 3) Weigh 80mg of silicon powder (30nm) and place it in a mortar. Grind it thoroughly with the above binder solution for 20-30 minutes. 4) Place the electrode paste obtained in step 3) onto the copper foil and apply it evenly with a scraper to fix the thickness; 5) The electrode was placed in a vacuum drying oven and dried at 80℃ for 12 h, then heated to 150℃ and held for 6 h before punching to obtain a circular electrode sheet with a diameter of 12 mm. The loading amount of silicon nanoparticles on the copper foil was controlled to be 0.8~0.9 mg / cm² by controlling the height of the coating doctor blade. -2 ; 6) Place the electrode obtained in step 5) in a glove box filled with argon gas, use a lithium metal sheet as the reference electrode, 1M LiPF6 (DMC:FEC=4:1 Vol%) as the electrolyte, and assemble a half cell with a diaphragm manufactured by Gelgard.

[0054] The electrode sheet prepared in this comparative example was cut into 10mm*40mm samples. The side of the electrode coated with the slurry was adhered to a steel sheet using 3M tape. The lower end of the sample was fixed on a tensile testing machine at room temperature and subjected to a tensile test at 100mm min. -1 A constant rate was used to perform a 180° peeling experiment on the electrode sheet. For example... Figure 2 As shown, the average peel force of the CP adhesive is 242 mN, which is lower than that of the CCP adhesive. This proves that citric acid, as a crosslinking agent, plays an important role in the in-situ chemical crosslinking of CMC and PEDOT:PSS to form a three-dimensional conductive network with strong adhesion and excellent mechanical properties.

[0055] The crosslinking density of the CP binder prepared with 0 wt% CA was determined by rheological testing. Figure 4 The changes in G′ and G′′ of polymer solutions with different amounts of crosslinking agent are shown as a function of frequency. By adjusting the crosslinking agent concentration to control the crosslinking density and network strength of the polymer solution, the CP binder exhibits a lower crosslinking density.

[0056] The charge-discharge performance of half-cells assembled using CP (CA=0) binder was tested using a LAND-CT3002A tester, with a current density of 2000 mA g. -1 Set the voltage range to 0.01~1.5V. For example... Figure 5 As shown, the Si / CP (CA=0) electrode at 2000 mA g -1At low current densities, the battery exhibits rapid capacity decay, with a capacity retention of only 0.3% after 300 cycles. This is because at a CA concentration of 0%, it is difficult for the linear polymer CMC and PEDOT:PSS to form a three-dimensional network structure through chemical interactions. During the repeated volume expansion and contraction of silicon particles, the linear polymer is prone to irreversible slippage, losing its electrical connection with the silicon particles. Simultaneously, the poor mechanical properties of the linear polymer binder are insufficient to buffer the enormous stress generated by the volume expansion of silicon particles, failing to maintain the integrity and stability of the electrode structure during cycling, leading to rapid capacity decay. Figure 6 As shown.

[0057] Comparative Example 4 Preparation of silicon electrodes using citric acid as a crosslinking agent and a polymer binder CCP (CA=2.5) at a concentration of 2.5 wt% and their application in lithium-ion batteries: 1) Dissolve 9 mg of CMC in deionized water to prepare a 9 wt% CMC solution; 2) Add 2.5 mg of CA to the above solution and stir to dissolve; 3) Add 6 mg of PEDOT:PSS to the above solution and stir for 3 hours until well mixed; 4) Weigh 80mg of silicon powder (30nm) and place it in a mortar. Grind it thoroughly with the above binder solution for 20-30 minutes. 5) Place the electrode paste obtained in step 4) onto the copper foil and apply it evenly with a scraper to fix the thickness; 6) The electrode was placed in a vacuum drying oven and dried at 80℃ for 12 h, then cross-linked in situ at 150℃ for 6 h before punching to obtain a circular electrode sheet with a diameter of 12 mm. The loading amount of silicon nanoparticles on the copper foil was controlled to be 0.8~0.9 mg / cm² by controlling the height of the coating doctor blade. -2 ; 7) Place the electrode obtained in step 6) in a glove box filled with argon gas, use a lithium metal sheet as the reference electrode, 1M LiPF6 (DMC:FEC=4:1 Vol%) as the electrolyte, and assemble a half cell with a diaphragm manufactured by Gelgard.

[0058] The crosslinking density of the CCP adhesive prepared with a CA addition ratio of 2.5 wt% was determined by rheological testing. Figure 4 The changes in G′ and G′′ of polymer solutions with different amounts of crosslinking agent are shown as a function of frequency. By adjusting the crosslinking agent concentration, the crosslinking density and network strength of the polymer solution can be controlled. Compared with CP, the crosslinking density of CCP (CA=2.5) binder is increased.

[0059] The charge-discharge performance of half-cells assembled using CCP (CA=2.5) binder was tested using a LAND-CT3002A tester, with a current density of 2000 mA g. -1 Set the voltage range to 0.01~1.5V. For example... Figure 5 As shown, compared to Si / CP (CA=0), the Si / CCP (CA=2.5) electrode at 2000 mA g -1 At a lower current density, it exhibits improved cycling stability, with a capacity retention of 25.88% after 300 cycles. This is because the CA concentration is 2.5%, at which point the crosslinking density of the polymer system is low, and the three-dimensional network structure formed by chemical crosslinking is sparse and loose, resulting in relatively poor mechanical properties. However, this allows the electrode structure to maintain relative integrity and stability during cycling. Figure 6 As shown.

[0060] Comparative Example 5 Preparation of silicon electrodes using citric acid as a crosslinking agent and a polymer binder CCP (CA=7.5) at a concentration of 7.5 wt% and its application in lithium-ion batteries: 1) Dissolve 9 mg of CMC in deionized water to prepare a 9 wt% CMC solution; 2) Add 7.5 mg of CA to the above solution and stir to dissolve; 3) Add 6 mg of PEDOT:PSS to the above solution and stir for 3 hours until well mixed; 4) Weigh 80mg of silicon powder (30nm) and place it in a mortar. Grind it thoroughly with the above binder solution for 20-30 minutes. 5) Place the electrode paste obtained in step 4) onto the copper foil and apply it evenly with a scraper to fix the thickness; 6) The electrode was placed in a vacuum drying oven and dried at 80℃ for 12 h, then cross-linked in situ at 150℃ for 6 h before punching to obtain a circular electrode sheet with a diameter of 12 mm. The loading amount of silicon nanoparticles on the copper foil was controlled to be 0.8~0.9 mg / cm² by controlling the height of the coating doctor blade. -2 ; 7) Place the electrode obtained in step 6) in a glove box filled with argon gas, use a lithium metal sheet as the reference electrode, 1M LiPF6 (DMC:FEC=4:1 Vol%) as the electrolyte, and assemble a half cell with a diaphragm manufactured by Gelgard.

[0061] The crosslinking density of the CCP adhesive prepared with a CA addition ratio of 7.5 wt% was determined by rheological testing. Figure 4The changes of G′ and G′′ in polymer solutions with different amounts of crosslinking agent are shown. By adjusting the crosslinking agent concentration to control the crosslinking density and network strength of the polymer solution, G′ increased by nearly four orders of magnitude throughout the polymerization process as the crosslinking agent concentration increased from 0 wt% to 7.5 wt%, indicating that the polymer system was highly crosslinked at this point. With increasing crosslinking agent concentration, the crosslinking density and network strength of the three-dimensional conductive network polymer increased. When the CA concentration was 7.5 wt%, G′ and G′′ were not correlated with frequency, proving that the polymer system was fully crosslinked. At this point, the polymer crosslinking density was the highest, forming the densest three-dimensional conductive network structure.

[0062] The charge-discharge performance of half-cells assembled using CCP (CA=7.5) binder was tested using a LAND-CT3002A tester, with a current density of 2000 mA g. -1 Set the voltage range to 0.01~1.5V. For example... Figure 5 As shown, the Si / CCP (CA=7.5) electrode at 2000 mA g -1 The Li exhibited the worst capacity retention at the lowest possible current density, with a capacity retention of only 0.17% after 300 cycles. This is because the polymer crosslinking density was highest at a CA concentration of 7.5%, resulting in an excessively dense polymer network on the silicon particle surface, which limited the Li... + The mechanical stress transported in the electrode and applied in reverse to the silicon particles during continuous lithiation increases with the increase of polymer network crosslinking density. After multiple cycles, the huge mechanical stress causes silicon particles to break, electrode structure to be damaged, and cycling performance to rapidly decline. Figure 6 As shown.

Claims

1. The application of an adaptive three-dimensional conductive binder in silicon-based lithium-ion batteries, characterized in that: The adaptive three-dimensional conductive binder uses citric acid as a crosslinking agent and is prepared by in-situ crosslinking of sodium carboxymethyl cellulose and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) during electrode preparation. The mass percentages of sodium carboxymethyl cellulose, citric acid, and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) added are 1~20 wt%: 1~20 wt%: 1~20 wt%. The crosslinking density of the adaptive three-dimensional conductive binder is adjusted by controlling the concentration of citric acid. Citric acid, as a crosslinking agent, covalently crosslinks with sodium carboxymethyl cellulose and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) through an esterification reaction during electrode preparation. The silicon electrode using the adaptive three-dimensional conductive binder is prepared through the following steps: S1) Dissolve sodium carboxymethyl cellulose in deionized water to prepare a 9 wt% sodium carboxymethyl cellulose solution; S2) Add 5 wt% citric acid and 6 wt% poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) sequentially to the sodium carboxymethyl cellulose solution and stir for 5 hours to completely dissolve and mix evenly; S3) Place the above binder solution and 80wt% silicon powder with a particle size of 30nm in a mortar and grind for 20~30min; S4) Place the above electrode paste on copper foil and apply it to the electrode using a doctor blade to fix the thickness; S5) Place the above electrodes in a vacuum drying oven and dry them at 80°C for 12 h, then crosslink them in situ at 150°C for 6 h. S6) Cut the cross-linked electrode into electrode discs with a diameter of 12 mm to obtain a silicon electrode using a three-dimensional conductive network polymer binder.

2. The adaptive three-dimensional conductive binder according to claim 1 in silicon-based lithium Its application in ion batteries is characterized by: The viscosity of the sodium carboxymethyl cellulose is ≥ 1900 mPa·s, the molecular weight of citric acid is 192.

3. The adaptive three-dimensional conductive binder according to claim 1 in silicon-based lithium Its application in ion batteries is characterized by: The coating thickness in step S4) is 10~30μm.

Citation Information

Patent Citations

  • Application of carboxymethyl chitosan self-crosslinking polymer in silicon negative electrode of lithium ion battery

    CN105702963A

  • Three-dimensional mixed conductive adhesive used for lithium battery, and battery containing adhesive

    CN109461937A

  • Three-dimensional network water-based composite binder and application thereof in lithium ion battery

    CN111180733A